Can uncertainty justify overlapping policy instruments to mitigate emissions? - Oskar Lecuyer; Philippe Quirion (Fondazione Eni Enrico Mattei (FEEM), 2012)
This article constitutes a new contribution to the analysis of overlapping instruments to cover the same emission sources. Using both an analytical and a numerical model, we show that when the risk that the CO2 price drops to zero and the political unavailability of a CO2 tax (at least in the European Union) are taken into account, it can be socially optimal to implement an additional instrument encouraging the reduction of emissions, for instance a renewable energy subsidy. Our analysis has both a practical and a theoretical purpose. It aims at giving economic insight to policymakers in a context of increased uncertainty concerning the future stringency of the European Emission Trading Scheme. It also gives another rationale for the use of several instruments to cover the same emission sources, and shows the importance of accounting for corner solutions in the definition of the optimal policy mix.
Keywords: Q28; Q41; Q48; Q58; 330; Uncertainty; Policy Overlapping; Mitigation Policy; Energy policy; EU-ETS; Renewable Energy; Corner Solutions; Nil CO2 Price; Klimaschutz; Emissionshandel; Policy-Mix; EU-Staaten